Electronics all-in-one for Dummies - Lowe, Doug, 1959- (--For dummies., 2022)
Open up a world of electronic possibilities with the easiest "how-to" guide available today If you're looking for a new hobby that's tons of fun--and practical to boot--electronics might be right up your alley. And getting started has never been easier! In Electronics All-in-One For Dummies, you'll find a plethora of helpful information, from tinkering with basic electronic components to more advanced subjects like working with digital electronics and Arduino microprocessors. Whether you're just getting started and trying to learn the difference between a circuit board and a breadboard, or you've got a handle on the fundamentals and are looking to get to the next level of electronics mastery, this book has the tools, techniques, and step-by-step guides you need to achieve your goals--and have a blast doing it! You'll learn: Critical safety tips and strategies to keep yourself and your environment protected while you work Useful schematics for everyday devices you can put to work immediately, like animated holiday lights and animatronic prop controllers How to work with alternating current, direct current, analog, digital, and car electronics, as well as Raspberry Pi technologies Perfect for anyone who's ever looked at a circuit board and thought to themselves, "I wonder how that works?", Electronics All-in-One For Dummies is your go-to guide to getting a grip on some of the coolest electronic technologies on the market.